Development and validation of a high performance liquid 4 chromatography method for oligodeoxynucleotides determination 5 in a novel coagel-based formulation - Ullio Gamboa, Gabriela Veronica (2015)
The therapeutic benefit of phosphorothioate oligodeoxynucleotides (PS-ODN) containing immune stimulatory sequences has been demonstrated in animal models of cancer and infection. Several tools are available for the determination of these oligonucleotides in biological samples and pharmaceutical preparations, including UV spectroscopy, dye binding, isotopic tracing, capillary gel electrophoresis (CGE), hybridization-based enzyme-linked immunosorbent assay (ELISA), and chromatography techniques. However, due to inter-assay variability and accuracy problems associated with the afore mentioned methods, we have developed and validated an isocratic high performance liquid chromatographic (HPLC) for analytical determination of PS-ODN containing unmethylated CpG motifs (CpG-ODN). Validation under Food and Drug Administration (FDA) guidelines of the analytical parameters include: linearity (r2 0.9996), LOD (0.86 lg/ml) and LOQ (6.25 lg/ml), intra (0.19?3.37%) and inter-day precision (0.63?3.75%) expressed as relative standard deviation (RSD), and robustness parameters (less than 2.80%). Using this method, recoveries ranging from 89.9% to 99.9% were obtained. Thus, this method provides a simple, sensitive, precise and reproducible examination which can be readily adapted for the assessment of CpG-ODN in different pharmaceutical preparations.